Analysis of Flow Over Streamlined Body of High-Speed Train and Bus - Aziz, Muhammad Afif Rifaie; Taib, Ishkrizat (Progress in Aerospace and Aviation Technology, 2025)
External aerodynamic flow is a key factor in determining the performance, energy efficiency, and stability of land-based vehicles such as trains and buses. Vehicles with streamlined shapes tend to experience less aerodynamic drag compared to blunt bodies, which are more prone to flow separation and larger wake regions. This study aims to investigate and compare the external flow behavior over a streamlined body and a blunt body using Computational Fluid Dynamics (CFD). The objective is to understand how shape influences boundary layer development, flow separation, wake formation, and overall drag characteristics. Two geometries are modeled: a high-speed train, representing the streamlined body, and a bus, representing the blunt body. The train model is scaled to a width of 0.3 m, height of 0.4 m, and length of 3.2 m, while the bus model has a width of 0.244 m, height of 0.37 m, and length of 1.127 m. The flow inlet is being compared under incompressible conditions at air flow speeds of 10 m/s, 20 m/s, and 30 m/s through the opening, using three different values. For an accurate representation of wall boundary layers, a mesh is organized with fewer elements near walls, and the k-? model of turbulence is used. To see how the external flow works over every geometry, both velocity contours and pressure distributions are evaluated. It is shown that the train’s reduced geometric dimensions lead to less detached flow and a tighter wake, which then causes less drag. Conversely, the basic design of buses causes the flow to divide earlier and spread, which allows for more resistance. The results indicate that body shape has a big impact on airflow and support using streamlined designs for higher aerodynamic performance in vehicles.